4th INTERNATIONAL FORUM ON COOPERATIVE LAW, COOPERATION, PRINCIPLE 61AND NET ZERO - Mills, Cliff (International Journal of Cooperative Law, 2024)
The world’s economies are founded on competition, which provides the framework for enterprise driven by the profit motive and the pursuit of private gain. Competing for growth results in humanity living beyond the limits of planetary boundaries, and many people falling short of meeting their basic needs. Achieving net zero requires a different approach.Cooperation provides an alternative economic foundation for enterprise, based on the pursuit of fairness and concern for the impact of enterprise. It enables cooperative arrangements founded on values and principles to replace commercial contracts concerned only with private rights. Principle 6 3was introduced to enable cooperation to achieve the scale needed to challenge the dominance of competition-based enterprise. It encourages cooperatives and other enterprises, public bodies and institutions to collaborate amongst each other and thereby to move to the next level: from cooperation within businesses to cooperation between businesses and other organisations. This paper is written from a UK perspective but its arguments will resonate with other jurisdictions in a number of respects.